Pengaruh Bentuk Geometri Papan Komposit Serbuk Kayu Terhadap Serapan Bising Ruang - Yudhanto, Ferriawan; Rachmawati, Putri; Yusuf, Mirza; Dhewanto, Santo Ajie (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2026)
This study aims to analyze the effect of variations in surface geometry on the acoustic performance of composite boards made from jackfruit sawdust waste. The material was combined with urea-formaldehyde adhesive and catalyst, then processed using a hot-press method at 160°C and 60 tons. The specimens were formed into four geometric variations, namely funnels, cones, tubes, and pillars, using a CNC machine. Tests were conducted using the impedance tube method over the frequency range of 200-1600 Hz to determine the sound absorption coefficient (α) and reflection coefficient (RC). The results show that the α value increases with increasing frequency. At low frequencies (200-400 Hz), the absorption capacity remains low but increases significantly at medium to high frequencies. The pillar geometry showed the best performance with a maximum α value of around 0.42 and the lowest reflection value. It indicates that modification of the surface geometry plays an important role in improving wave interaction and the effectiveness of sound absorption.